(untitled) (Eastern Journal of Medical Sciences, 2021)
Addition of antibacterial agents to conventional glass-ionomer cement (GIC) eliminates the recurrence of decay around margins of restoration by inhibiting growth of microbial colonies. Objective: The objective of the study was to comparatively evaluate the antibacterial activity of GIC impregnated with betadine, probiotic, and chlorhexidine (CHX) powder against Streptococcus mutans. Materials and Methods: Chlorhexidine, betadine, and probiotic powder were added to GIC powder to achieve 2.5% CHX-GIC, 2.5% betadine-GIC, and 2.5% probiotic-GIC formulation. Fuji-IX GIC was used as a negative control. The powder and liquid were mixed and inserted in to the wells punched in agar plates. The antibacterial activity of cements was assessed at day 1, day 7, and day 15 using agar diffusion method. Results: There was no inhibition zone present on bacterial plates with control GIC. On day 1, mean inhibition zone against S. mutans was highest with probiotic-GIC (11.70±0.48 mm), followed by betadine-GIC (10.70±0.48 mm) and CHX-GIC (2.70±1.9 mm). On day 7, mean inhibition zone with probiotic-GIC was 5.30±0.83 mm, betadine-GIC was 3.50±0.71 mm, and CHX-GIC was 1.8±1.03 mm. No inhibition zone was observed with any group on day 15. Wilcoxon signed-rank test showed a significant difference in the inhibition zones on day 1 and day 7 with probiotic-GIC (p=0.0001) and betadine-GIC (p=0.001). Significant difference was observed between groups using Kruskal–Wallis test and post hoc Bonferroni tests (p<0.05). Conclusion: Probiotic-GIC, betadine GIC is more effective against S. mutans. With its enhanced antimicrobial effect, these cements can be considered as an alternative to the conventional GIC’S.